S-glutathionylation of buccal cell proteins as biomarkers of exposure to hydrogen peroxide - Grek, Christina L. (BBA Clin, 2014)
BACKGROUND: Exogenous or endogenous hydrogen peroxide (H(2)O(2)) is a reactive oxygen species (ROS) that can lead to oxidation of cellular nucleophiles, particularly cysteines in proteins. Commercial mouthwashes containing H(2)O(2) provide the opportunity to determine clinically whether changes in S-glutathionylation of susceptible proteins in buccal mucosa cells can be used as biomarkers of ROS exposure. METHODS: Using an exploratory clinical protocol, 18 disease-free volunteers rinsed with a mouthwash containing 1.5% H(2)O(2) (442 mM) over four consecutive days. Exfoliated buccal cell samples were collected prior and post-treatment and proteomics were used to identify S-glutathionylated proteins. RESULTS: Four consecutive daily treatments with the H(2)O(2)-containing mouthwash induced significant dose and time-dependent increases in S-glutathionylation of buccal cell proteins, stable for at least 30 min following treatments. Elevated levels of S-glutathionylation were maintained with subsequent daily exposure. Increased S-glutathionylation preceded and correlated with transcriptional activation of ROS sensitive genes, such as ATF3, and with the presence of 8-hydroxy deoxyguanosine. Data from a human buccal cell line TR146 were consistent with the trial results. We identified twelve proteins that were S-glutathionylated following H(2)O(2) exposure. CONCLUSIONS: Buccal cells can predict exposure to ROS through increased levels of S-glutathionylation of proteins. These post-translationally modified proteins serve as biomarkers for the effects of H(2)O(2) in the oral cavity and in the future, may be adaptable as extrapolated pharmacodynamic biomarkers for assessing the impact of other systemic drugs that cause ROS and/or impact redox homeostasis. GENERAL SIGNIFICANCE: S-glutathionylation of buccal cell proteins can be used as a quantitative measure of exposure to ROS.